Pengaruh Collateralizable Assets, Investment Opportunity Set, dan Growth In Net Asset Terhadap Kebijakan Dividen pada Perusahaan Food and Beverages - Sri Dedari Sandatijaya; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2021)
This study was conducted to examine the effect of collateralizable assets, investment opportunity set, and growth in net assets on dividend policy. This study uses a quantitative approach in the form of numbers from the variables used. The population of this study is food and beverages companies listed on the Indonesia Stock Exchange in the period 2016-2020. The sample of this research was obtained as many as 9 companies using purposive sampling technique. Data is collected from the company's financial statements by looking at the income statement, notes to financial statements, and statements of financial position. Then the data obtained were analyzed using descriptive statistical analysis, classical assumption test and multiple linear regression analysis assisted by the SPSS V20 program. The results of this study indicate that collateralizable assets have a significant positive effect on dividend policy, investment opportunity sets have a significant positive effect on dividend policy, and growth in net assets has a significant positive effect on dividend policy.